Increasing Referendum Participation in Accordance with the Philosophy of Samsen Resident’s in Thailand - Barameeboon Sangchan (Universitas Muhammadiyah Sidoarjo, 2018)
Following the referendum on the draft Constitution of the Kingdom of Thailand B.E. which was held on 7 August 2016, it revealed that most voters approved this draft constitution. Nevertheless, in this study of Samsen Community’s people who voted, they have their opinions about the political structure which are; Thailand is ready for the 2-party system, the qualification of the candidate should be graduated with a bachelor’s degree, and the head of the government should come from the party with a majority vote. Additionally, they disagree about the prime minister who comes from the senator’s nomination, and the senator should not have the authority of controlling the independent entity.